Newborn Screening for Primary Immune Deficiencies with a TREC/KREC/ACTB Triplex Assay-A Three-Year Pilot Study in Sweden - Rolf H. Zetterström; Michela Barbaro; Annika Ohlsson; Stephan Borte; Susanne Jonsson; Jacek Winiarski; Ulrika von Döbeln; Lennart Hammarström (MDPI AG, 2017)
Background: Screening newborns for severe combined immunodeficiency (SCID) has become essential, since efficient methods to identify infants with these disorders exist and early stem cell transplantation is life-saving. Method: We performed a three-year screening trial in Stockholm comprised of 89,462 newborn infants. The number of T-cell receptor excision circle (TREC)/kappa-deleting recombination excision circle (KREC)/β-actin (ACTB) copies were quantified simultaneously by real time polymerase chain reaction (PCR) in 3.2 mm punches from dried blood samples taken in the regular neonatal screening program. Results: Five patients with immune deficiencies were identified: two with SCID caused by mutations in the Artemis- and adenosine deaminase gene, respectively, one with ataxia telangiectasia and two with reversible agammagloblinemia, which so far, is of unknown cause. This points to an incidence of SCID at the same level as in other studies (around 1:50,000). In 19 recalled infants, low KREC levels and in one case, also low TREC levels, were caused by immunosuppressive treatment of the mother during pregnancy. The levels normalized within a month in all these infants. The total recall rate was 0.10%, and 40% of the recalled infants were born prematurely (<37 weeks gestation). Among 69 patients with inborn errors of metabolism screened retrospectively, only two, who were severely ill with organic acidemias when the sample was taken, and two with mitochondrial disorders, screened positive.